Perancangan Website Berbasis Design Thinking untuk Pasar Ikan Hias Parung Bogor - Sagita, Andi; Danny Sianggaputra, Muhammad; Dwi Agustian, Sulistyana; Sekarsih Ristyasmoro, Kenanda; Taryana, Asep (Jurnal Pengabdian Masyarakat STIE Surakarta, 2024)
This study develops a website for marketing ornamental fish at the Parung Ornamental Fish Market, Bogor, to improve user experience and marketing effectiveness. Despite daily transactions exceeding 1 billion rupiahs, digital technology adoption remains low. Using a design thinking approach—empathize, define, ideate, and prototype—this study collects data through field observations, content analysis, and literature review. Findings highlight challenges such as low digital literacy, limited infrastructure, and dependence on offline transactions. Meanwhile, consumers seek better access to product information, pricing, and availability. The proposed solution includes a responsive, user-friendly website with features like category navigation, aesthetic design, fish care guides, and social media integration. A mind map-based prototype outlines the information structure, key features, and visual elements. This study contributes significantly by enhancing the Parung Ornamental Fish Market's global competitiveness, expanding market reach, and fostering consumer trust through improved user experience and effective digital marketing.